Selection and preliminary evaluation of laboratory cracking tests for routine asphalt mix designs. (27th January 2017) - Zhou, Fujie; Im, Soohyok; Hu, Sheng; Newcomb, David; Scullion, Tom
Abstract : Cracking has become a primary mode of distress in recent years that frequently drives the need for rehabilitation of asphalt pavements. Meanwhile, asphalt mix designs are becoming more and more complex with the increasing uses of recycled materials, recycling agents, binder additives/modifiers, and multiple warm mix asphalt technologies. Thus, there is an urgent need to identify reliable cracking tests that can be used for routine mix design to eliminate brittle mixes. This paper critically reviewed cracking mechanisms and laboratory tests. A total of 12 cracking tests were discussed at a cracking test workshop held as part of the National Cooperative Highway Research Program Project 9-57. Seven cracking tests were selected for further laboratory evaluation and field validation. Four of the simpler cracking tests from the seven were evaluated in this paper, these being the Texas Overlay Test (OT), Disk-shaped Compact Tension (DCT) test, Semi-Circular Bend test from the Louisiana Transportation Research Center (SCB-LTRC), and SCB test at room temperature from Illinois (SCB-IL). A laboratory sensitivity study was performed, and the results showed that all four cracking tests were generally sensitive to asphalt mix components. However, there were some concerns with the DCT, SCB-LTRC, and SCB-IL. Both the DCT and SCB-IL were found to be not sensitive to asphalt binder content; and both the DCT and SCB-LTRC showed an unexpected increase in cracking resistance when adding RAS to the mix. Additionally, two sets of field test sections were used for preliminary validation of these four cracking tests. It was found that the OT, DCT, and SCB-IL provided rankings which matched the measured field performance for the two sections on US62, Texas; and the OT and SCB-LTRC were valid for six APT test sections. Further validation with different mixes, traffic, and climate is needed.